2021
DOI: 10.5194/aab-64-199-2021
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and sex on carcass characteristics and chemical composition of the longissimus thoracis et lumborum muscle in wild boars (<i>Sus scrofa</i>)

Abstract: Abstract. The aim of this study was to determine the influence of age and sex on carcass characteristics and the chemical composition of the longissimus thoracis et lumborum (LTL) muscle in wild boars (Sus scrofa). Carcass quality parameters varied significantly depending on age and sex, whereas the protein and collagen contents in the muscle were affected by animal age. The carcasses of male yearlings and adults were characterised by the highest processing suitability, which can be attributed to the highest p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Dominik et al [56] found significant (p < 0.05) difference (5.70 mg/g vs. 10.13 mg/g) only in the content of total collagen between leg (m. gluteus medius) and shoulder (m. triceps brachii) of farmed fallow deer (Dama dama), while the proportion of soluble collagen was comparable in both muscles (27.93% and 24.42%, respectively). The collagen content in wild boar loin (m. longissimus thoracis et lumborum) was significantly higher in boars up to 1 year (8 mg/g) compared with animals aged between 1 and 3 years (6 mg/g) [57]. A lower content of total collagen compared to the presented results obtained for beavers was also reported by the authors for the muscles of domestic animals.…”
Section: Collagen Fractions and Shear Forcesupporting
confidence: 78%
See 1 more Smart Citation
“…Dominik et al [56] found significant (p < 0.05) difference (5.70 mg/g vs. 10.13 mg/g) only in the content of total collagen between leg (m. gluteus medius) and shoulder (m. triceps brachii) of farmed fallow deer (Dama dama), while the proportion of soluble collagen was comparable in both muscles (27.93% and 24.42%, respectively). The collagen content in wild boar loin (m. longissimus thoracis et lumborum) was significantly higher in boars up to 1 year (8 mg/g) compared with animals aged between 1 and 3 years (6 mg/g) [57]. A lower content of total collagen compared to the presented results obtained for beavers was also reported by the authors for the muscles of domestic animals.…”
Section: Collagen Fractions and Shear Forcesupporting
confidence: 78%
“…The results obtained in the presented study indicate that beaver muscles contain more total and soluble collagen compared to the muscle tissue of other game species such as red deer [55], fallow deer [56] or wild boar [57]. The total collagen content and the percentage of water-soluble collagen in m. longissimus of red deer were 6.33 mg/g and 9.01% [55].…”
Section: Collagen Fractions and Shear Forcementioning
confidence: 90%
“…The reason for the large variation in weight for wild boars can be due to such factors as age, availability of feed and individual variations. Ludwiczak et al [ 23 ] also found a similar variation in juveniles and sub-adult wild boars between 24 and 60 kg measured as dressed field weight, and Zmijewski & Modzelewska-Kapitula [ 13 ] found a variation from 18 to 62 kg between 1- and 3-year-old animals. The pigs, on the other hand, are produced under controlled conditions, were of the same breed and were slaughtered at about the same age and weight, which gives a more homogeneous carcass weight.…”
Section: Resultsmentioning
confidence: 83%
“…However, the variations in the quality of wild boar meat, especially sensory aspects such as colour, taste, odour and tenderness are expected to be high due to the fact that the animals have quite a variation in diet depending on the region they live in and over the year (due to different feed sources available depending on the season) [ 12 ], as well as hunting techniques used, the gender of the animals and their age at slaughter [ 13 , 14 ]. Mature boars could develop so-called boar taint, an unpleasant odour caused by androstenone and skatole and other compounds [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%